Association of newer definitions of bronchopulmonary dysplasia with pulmonary hypertension and long-term outcomes - Hwang, Jae Kyoon; Shin, Seung Han; Kim, Ee-Kyung; Kim, Seh Hyun; Kim, Han-Suk (Frontiers in Pediatrics, 2023)
Background: The definition of bronchopulmonary dysplasia (BPD) has been evolved recently from definition by the National Institute of Child Health and Human Development in 2001 (NICHD 2001) to the definition reported in 2018 (NICHD 2018) and that proposed by Jensen et al. in 2019 (NICHD 2019). The definition was developed based on the evolution of non-invasive respiratory support and to achieve better prediction of later outcomes. Our objective was to evaluate the association between different definitions of BPD and occurrence of pulmonary hypertension (PHN) and long term outcomes. Methods: This retrospective study enrolled preterm infants born at < 32 weeks of gestation between 2014 and 2018. The association between re-hospitalization owing to a respiratory illness until a corrected age (CA) of 24 months, neurodevelopmental impairment (NDI) at a CA of 18–24 months, and PHN at a postmenstrual age (PMA) of 36 weeks was evaluated, with the severity of BPD defined based on these three definitions. Results: Among 354 infants, the gestational age and birth weight were the lowest in severe BPD based on the NICHD 2019 definition. In total, 14.1% of the study population experienced NDI and 19.0% were re-hospitalized owing to a respiratory illness. At a PMA of 36 weeks, PHN was identified in 9.2% of infants with any BPD. Multiple logistic regression analysis showed that the adjusted odds ratio (OR) for re-hospitalization was the highest for Grade 3 BPD of the NICHD 2019 criteria (5.72, 95% confidence interval [CI]: 1.37–23.92), while the adjusted OR of Grade 3 BPD was 4.96 (95% CI: 1.73–14.23) in the NICHD 2018 definition. Moreover, no association of the severity of BPD was found in the NICHD 2001 definition. The adjusted ORs for NDI (12.09, 95% CI: 2.52–58.05) and PHN (40.37, 95% CI: 5.15–316.34) were also the highest for Grade 3 of the NICHD 2019 criteria. Conclusion: Based on recently suggested criteria by the NICHD in 2019, BPD severity is associated with long-term outcomes and PHN at a PMA of 36 weeks in preterm infants.